Local and systemic gene expression levels of IL-10, IL-17 and TGF-β in active ocular toxoplasmosis in humans. (October 2021) - Raouf-Rahmati, Amene; Ansar, Amir-Reza; Rezaee, Seyed Abdolrahim; Hosseini, Seyedeh Maryam; Garweg, Justus G.; Ghezeldasht, Sanaz Ahmadi; Vaghei, Soheila; Zarean, Mehdi; Shamsian, Seyed Aliakbar; Moghaddas, Elham
Highlights: Gene expression in AH and PBMC in active ocular toxoplasmosis and controls. While the expression for IL-10 and IL-17 in the AH was increased, TGF-β was decreased. Expression for IL-10, IL-17 and TGF-β in AH followed an opposite pattern compared to PBMC. The expression levels for IL-17 in PBMC was not upregulated. Our results strongly indicate an underlying local rather than a systemic immune regulation. Abstract: Background: To compare mRNA expression of interleukin 10 (IL-10), interleukin 17 (IL-17) and Transforming Growth Factor-β (TGF-β) in aqueous humor (AH) and peripheral blood mononuclear cells (PBMCs) in human ocular toxoplasmosis (OT) and controls. Method: RNA isolation, cDNA synthesis and real-time polymerase chain reaction were performed on AH sediments and PBMCs of 16 patients with active OT and 21 controls at the Khatam-al-Anbia Eye Hospital, Iran. For comparison, Mann Whitney U test was used at a discrimination level of p < 0.05. Pearson and Spearman rank correlation test were applied for correlation with clinical parameters. Results: The expression for IL-10 and IL-17 in the AH was 3.7- and 88.0-fold higher in OT than in controls (P = 0.04 and P = 0.03, respectively) whereas that of TGF-β was 7.7-fold lower (P < 0.001). The expression levels for these cytokines in PBMC followed a similar pattern (IL-10 13.8-fold down-regulated (P = 0.001), IL-17 with 1.9-fold insignificantly upregulated (p = 0.43), TGF-β 452.8-fold down-regulated (P = 0.002). Compared to PBMC, IL-10 coding mRNA was 1876-fold higher in the almost cell-free AH in OT (39.2-fold in controls), IL-17 coding mRNA was 9.4-fold higher (17.7-fold down-regulated in controls), and that coding for TGF-β 207-fold higher in OT (7x10 5 -fold in controls). The expression for IL-10, IL-17 and TGF-β in AH thus followed an opposite pattern compared to that in PBMC. Conclusion: OT induces a highly-specific local immunoregulatory process as evidenced by an intraocular up-regulation of IL-10 and down-regulation of TGF-β mRNA. This could indicate an attempt to prevent unnecessary tissue damage which is in line with a moderate local mRNA up-regulation for IL-17 which seems sufficient to control parasite proliferation. That this regulation is opposite to that in PBMC may be linked to intraocular immune deviation in the course of disease.